Pengaruh Budaya Organisasi dan Iklim Organisasi terhadap Kepuasan Kerja dan Dampaknya terhadap Kinerja Pegawai pada Badan Kesatuan Bangsa dan Politik Provinsi DKI Jakarta - I Gusti Ayu Pradnya Paramitha; Lies Putriana; Choirul Maksum (JURNAL CITRA WIDYA EDUKASI, 2019)
Every organization has its own goals, but basically every organization has the same goal of obtaining maximum results for its efforts. This study aims to determine the influence of organizational culture and organizational climate on job satisfaction and its impact on employee performance. Data collection is done by online questionnaires to companies. Data of 132 respondents were used as samples of this study and SEM analysis using smartPLS 3. The results of data analysis showed that Organizational Culture has an influence on the satisfaction of Employee Work, Organizational Climate has an influence on employee job satisfaction. Organizational culture has no influence on employee performance, organizational climate has an influence on employee performance, job satisfaction has an influence on employee performance.